2021
DOI: 10.1101/2021.10.04.463067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

REV7/FANCV Binds to CHAMP1 and Promotes Homologous Recombination Repair

Abstract: A critical determinant of DNA repair pathway choice is the HORMA protein REV7, a small abundant adaptor which binds to various DNA repair proteins through its C-terminal seatbelt domain. The REV7 seatbelt binds to the REV3 polymerase to form the Polymerase ζ complex, a positive regulator of translesion synthesis (TLS) repair. Alternatively, the REV7 seatbelt binds to SHLD3 in the Shieldin complex, a positive regulator of NHEJ repair. Recent studies have identified another novel REV7 seatbelt-binding protein… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…A recent study suggests CHAMP1 along with REV7 is involved in DNA repair regulation. High levels of CHAMP1 favoured HR repair pathway in cells subjected to DNA DSBs using high doses of UV radiation (Li et al, 2021). Moreover, CHAMP1-REV7 complex formation is crucial for activation of HR pathway.…”
Section: Rev7 In Shieldin Complexmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study suggests CHAMP1 along with REV7 is involved in DNA repair regulation. High levels of CHAMP1 favoured HR repair pathway in cells subjected to DNA DSBs using high doses of UV radiation (Li et al, 2021). Moreover, CHAMP1-REV7 complex formation is crucial for activation of HR pathway.…”
Section: Rev7 In Shieldin Complexmentioning
confidence: 97%
“…A recent study identified a conserved Threonine at position 103 to be target for phosphorylation (Li et al, 2021). Moreover, the phosphorylated form of REV7 was enriched in the chromatin bound fractions as opposed to nonchromatin bound fractions.…”
Section: Potential Catalytic Factors For Shieldin Assemblymentioning
confidence: 98%